Complete Genome Sequences of Lactobacillus Strains C25 and P38, Isolated from Chicken Cecum - Hassan, Hosni M. (Microbiol Resour Announc, 2020)
We report the complete circular genome sequences of Lactobacillus crispatus strain C25, its plasmid, and Lactobacillus animalis strain P38; both strains were isolated from the cecum of 4-week-old chickens. These isolates represent potential probiotic strains for poultry.